Moderate Islam in Indonesia Foreign Policy Towards Cases with Islamic Dimension in European Countries - Andi Purwono (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Introduction Some problems are facing European countries like migration from middle east conflict countries. Another axample is terror attacks like what have happened in London and Paris assault, Charlie Hebdo office attack in 7th of January 2015 and also Stadium Stade de France Paris attack in 13rd November 2015 that killed 120 people and dozens injured. Even French President Hollande declared a state of national emergency. At the otherside, we can see islamophobia and misperception towards Islam also arise. Some cases of islamic blasphemy like publication of prophet cartoon in Danish magazine Jylland Posten, its duplication in many media, and film Fitna cretaed by Geert Wilder can be mentioned.